Peningkatan Pendapatan Keluarga Melalui Pelatihan Wirausaha Produk Olahan Makanan - Khotim Fadhli; Ita Rahmawati; Bekti Widyaningsih; Laila Rohmatun Nazila; Naufal Dhiyaaulhaq; Ahmad Baihaqiyullah Asazilli Islam (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2024)
Family income is one of the important things that needs to be increased as an effort to improve welfare. This community service is carried out through three stages, namely design, implementation of activities, and evaluation. Community service activities with PKK partners in Dukuharum village, Megaluh sub-district, Jombang district, East Java, in the form of entrepreneurial training for processed food products for housewives attended by 30 people, had a positive effect on efforts to increase family income. After implementing entrepreneurial training for processed food products for housewives as an effort to improve the family economy in Dukuharum village, Megaluh sub-district, Jombang district, East Java, it has increased the knowledge of housewives about entrepreneurship and culinary business opportunities and has helped increase the income of housewives through business. home or culinary business. Keywords: Training, Entrepreneurship, Products, Income